(untitled) (The International Journal for Scientific Research, 2025)
This paper analyzes the efficiency structure of Sudan agriculture in farm household level by using of stochastic frontier analysis model and Tobit model. A household level survey is used in the analysis. Using designed questionnaire for a sample of 100 farmers from 11 localities in Gadarif- State, Sudan. By using these estimates, relative importance of inputs and their interaction with various farm characteristics are inspected. The efficiency scores are estimated at farm household level. Has ranged from as low as 25% to as high as 100%. The average was 54%. The resultant average technical efficiency indicate that there is scope for increasing sorghum production by 46% with the present level of inputs and technology. Tobit model results showed that age and education are significant and negative but for seed source, that is significant and positive on technical efficiency, these factors represent the good characteristics that increase to or remove from efficiency. The main findings from this analysis was there is possibility to enhance the efficiency of sorghum producers in the study area, By approving good management practices and proper distribution of the existing resources and technology, along with extension programmes, the potential that exists for improving the productivity of sorghum in the Gadarif state, could be exploited. And also that the technical efficiency of sorghum farmers could be improved by practicing best use of inputs and improving the inefficiency factors